Time-limited counselling. - Feltham, Colin (London : Sage Publications, 1997)
Outlines the specific practical and technical skills, strategies and knowledge counsellors must have in order to undertake time-limited counselling. Following an examination of the client's induction into counselling, this book describes the appropriate models for different clients and problems
Includes bibliographical references and index.
Keywords: Short-term counseling; Political science -- Public Policy -- Social Services & Welfare; Social science -- Human Services